Analisis Pengaruh Penerapan Total Quality Management Dan Just In Time Pada Industri Manufaktur (Studi Empiris Pada Perusahaan Manufaktur Di Bogor Dan Tangerang) - Linda Santioso; Cynthia Maharani (Jurnal Ekonomi, 2015)
As we know the main value to be achieved by a company is to meet the desires of its customers. Total Quality Management represents the creation of value by basing on the quality provided to consumers, while Just In Time creates value based on a given speed. The manufacturing industry is an industry that is becoming an important part of the national economy, but some manufacturing companies in Indonesia implementing TQM and JIT just still a concept. This study tries to analyze the impact of the implementation of Total Quality Management and Just In Time for Delivery Performance. The variables used in this study include Total Quality Management and Just In Time as an independent variable, and Delivery Performance as the dependent variable. The research methodology used in this study is a survey method using a questionnaire as a data collection tool. This study used a sample of 6 manufacturing companies located in Bogor and Tangerang. The results of the analysis using the regression model showed that Total Quality Management and Just In Time has a significant impact on Delivery Performance.